Answer: The recursive equation for this sequence is t(n+1)=t(n) - 3.
Explanation:
The recursive equation for the given sequence is t(n+1) = t(n) - 3. This means that to find the next term in the sequence, we take the previous term and subtract 3 from it.
For example:
t(1) = 8 (first term in the sequence)
t(2) = t(1) - 3 = 8 - 3 = 5 (second term in the sequence)
t(3) = t(2) - 3 = 5 - 3 = 2 (third term in the sequence)
t(4) = t(3) - 3 = 2 - 3 = -1 (fourth term in the sequence)
In general, the recursive equation t(n+1) = t(n) - 3 will give the nth term of the sequence.
It should be noted that the initial condition provided in the question t(0)=-3, t(n+1)=t(n) +11 is incorrect and will not give the same sequence.